Prognostic Value of Pro-Inflammatory Neutrophils and C-Reactive Protein in Cancer Patient With Coronavirus Disease 2019: A Multi-Center, Retrospective Study - Zhang, Bo; Yu, Yuanhang; Hubert, Shawna M.; Zhang, Yue; Lu, Jianhua; Liu, Shihua; Xie, Fang; Zhao, Liang; Lei, Xiao; Deng, Wei; Chen, Jianying; Li, Yunqiao (Frontiers in Pharmacology, 2020)
Background: At present, the epidemic of the novel coronavirus disease 2019 (COVID-19) has quickly engulfed the world. Inflammatory cytokines are associated with the severity and outcomes of patients with COVID-19. However, the prognostic value of pro-inflammatory factors in cancer patients with COVID-19 are unknown. Methods: A multi-center, retrospective, cross-sectional study, based on 5 designated tertiary hospitals for the treatment of COVID-19 in Hubei Province, China. 112 cancer patients with COVID-19, and 105 COVID-19 patients without cancer were enrolled in the study between January 1st, 2020 and April 30th, 2020. The risk assessment of pro-inflammatory factors for disease severity and clinical adverse outcomes was identified by univariable and multivariable logistic regression models. Results: Of the 112 cancer patients with COVID-19, 40 (35.7%) patients were in critical condition and 18 (16.1%) patients died unfortunately. Univariate and multivariate analysis demonstrated that hemoglobin level and pro-inflammatory neutrophils and C-reactive protein, can be used as independent factors affecting the severity of COVID-19; Meanwhile, pro-inflammatory neutrophils and C-reactive protein can be used as an independent influencing factor for adverse clinical outcome of death. Moreover, the dynamic changes of neutrophils and C-reactive protein were also presented, and compared with COVID-19 patients without cancer, cancer patients with COVID-19 showed higher neutrophil counts and C-reactive protein levels. Conclusions: In cancer patients with COVID-19, the significant increase in pro-inflammatory neutrophils and C-reactive protein indicated a more critical illness and adverse clinical outcome, and pro-inflammatory neutrophils and C-reactive protein played a greater adverse role compare with COVID-19 patients without cancer, which may be the cause of critical illness and adverse clinical outcomes of cancer patients with COVID-19.